Loneliness and its opposite : sex, disability, and the ethics of engagement - Kulick, Don; Rydström, Jens (Duke University Press, 2015)
Don Kulick and Jens Rydström argue that for people with disabilities, being able to explore their sexuality is an issue of fundamental social justice. The authors analyze how Sweden and Denmark engage with the sexuality of people with disabilities; whereas Sweden hinders sexuality, Denmark supports it through the work of third-party sexual helpers.